Human Resource Management for Competency Development in Vocational Higher Education. - Yu Shui; Karta Sasmita; Linda Ika Mayasari (Teunuleh Publisher, 2026)
Human resource development is crucial for enhancing the quality of vocational higher education. Yet, many vocational higher education institutions struggle with Human Resource Management (HRM), especially in empowering lecturers, developing teaching staff skills, evaluating performance effectively, and aligning HRM policies with institutional needs. This study examines how HRM practices affect lecturer empowerment and staff skill development at Lanzhou Vocational College of Engineering (LVCE), China. It uses a mixed-methods approach with an explanatory sequential design. A total of 120 lecturers and staff participated in the research. Quantitative data were analyzed using descriptive statistics, Pearson’s correlation, and multiple regression, while qualitative data were gathered through in-depth interviews and analyzed using thematic analysis. The results show that HRM practices significantly impact lecturer empowerment, explaining 46% of the variance (R² = 0.46; p < 0.001). Training and development were the most influential factors (? = 0.39), followed by performance management (? = 0.28), recruitment and selection (? = 0.21), and the compensation system (? = 0.18). Qualitative findings indicate that while the HRM system is well-structured, it faces challenges like output-focused performance evaluation, low lecturer involvement in decision-making, and limited customization of training programs. This research is novel in integrating Strategic Human Resource Management, Human Capital Theory, and lecturer empowerment perspectives within the context of vocational higher education in China, using a mixed-methods approach to create a strategic HRM development model focused on continuous skill enhancement.